Anti-Bullying Characters Based on Hadith: Controlling Your Mouth and Hands: Karakter Anti Bullying Berbasis Hadis: Mengendalikan Lisan Dan Tangan - Saifullah, Saifullah; Hadi , Muhammad Fazlurrahman; Cahyadi , Rahmat Arofah Hari (Halaqa: Islamic Education Journal, 2025)
The phenomenon of bullying in the educational environment continues to be a serious concern because of its detrimental impact on students' mental, social and spiritual development. From an Islamic perspective, bullying behavior is contrary to teachings that emphasize love, respect and protection of others. One of the important guidelines in building an anti-bullying character is the hadith of the Prophet Muhammad, which reads: "A Muslim is a person whose words and hands are safe from other people." This research aims to integrate the values ​​contained in the Prophet's hadiths into students' character building strategies so that they have an anti-bullying attitude. This study employs qualitative and quantitative methods. In-depth interviews and text analysis provided qualitative data, while surveys provided quantitative data. Qualitative research shows that this hadith can guide character education programs, and quantitative research shows that 80% of students believe that understanding this hadith can prevent bullying, and 65% believe that hadith-based training can increase empathy. This hadith may be used to promote anti-bullying character education in schools in numerous ways. for example, by holding teacher training, compiling special modules and involving students in building anti-bullying character. The conclusion of this research confirms that hadith-based character education not only provides a solution to overcoming the problem of bullying, but is also an effort to form a generation that has high moral awareness and is able to maintain peaceful social relations. Highlights: Hadith-Based Approach: The study highlights the importance of Islamic teachings, particularly the hadith, in fostering anti-bullying character education. Empathy Development: 65% of students believe that hadith-based training improves their empathy, reducing bullying behavior. Implementation Strategies: Schools can apply this approach through teacher training, special curriculum modules, and student involvement programs. Keywords: Anti-Bullying, Character, Hadith